4(x-3)-3(x-1)=2(x-1)-3(x+1)

Simple and best practice solution for 4(x-3)-3(x-1)=2(x-1)-3(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)-3(x-1)=2(x-1)-3(x+1) equation:


Simplifying
4(x + -3) + -3(x + -1) = 2(x + -1) + -3(x + 1)

Reorder the terms:
4(-3 + x) + -3(x + -1) = 2(x + -1) + -3(x + 1)
(-3 * 4 + x * 4) + -3(x + -1) = 2(x + -1) + -3(x + 1)
(-12 + 4x) + -3(x + -1) = 2(x + -1) + -3(x + 1)

Reorder the terms:
-12 + 4x + -3(-1 + x) = 2(x + -1) + -3(x + 1)
-12 + 4x + (-1 * -3 + x * -3) = 2(x + -1) + -3(x + 1)
-12 + 4x + (3 + -3x) = 2(x + -1) + -3(x + 1)

Reorder the terms:
-12 + 3 + 4x + -3x = 2(x + -1) + -3(x + 1)

Combine like terms: -12 + 3 = -9
-9 + 4x + -3x = 2(x + -1) + -3(x + 1)

Combine like terms: 4x + -3x = 1x
-9 + 1x = 2(x + -1) + -3(x + 1)

Reorder the terms:
-9 + 1x = 2(-1 + x) + -3(x + 1)
-9 + 1x = (-1 * 2 + x * 2) + -3(x + 1)
-9 + 1x = (-2 + 2x) + -3(x + 1)

Reorder the terms:
-9 + 1x = -2 + 2x + -3(1 + x)
-9 + 1x = -2 + 2x + (1 * -3 + x * -3)
-9 + 1x = -2 + 2x + (-3 + -3x)

Reorder the terms:
-9 + 1x = -2 + -3 + 2x + -3x

Combine like terms: -2 + -3 = -5
-9 + 1x = -5 + 2x + -3x

Combine like terms: 2x + -3x = -1x
-9 + 1x = -5 + -1x

Solving
-9 + 1x = -5 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-9 + 1x + x = -5 + -1x + x

Combine like terms: 1x + x = 2x
-9 + 2x = -5 + -1x + x

Combine like terms: -1x + x = 0
-9 + 2x = -5 + 0
-9 + 2x = -5

Add '9' to each side of the equation.
-9 + 9 + 2x = -5 + 9

Combine like terms: -9 + 9 = 0
0 + 2x = -5 + 9
2x = -5 + 9

Combine like terms: -5 + 9 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 4t=240 | | 3n-35=79 | | 3r=81 | | 8(x-9)=3(x-4) | | 16-2x=19-4x | | 9d=72 | | f(x)=2x^2+9x-1 | | 9/x+3=0 | | f(x)=81 | | 7x/y=41 | | 16r=0.8Y | | 7a+2a+3b+3b= | | X=0.8Y-16r | | 5/7y+2/7=4 | | X+2=-x-7 | | (16x^2-8)=81 | | 13x=-12+10x | | d+2.7t=-4.8t-6 | | 5v^2=35v | | 4x+8x=9-5x | | x^3-21x^2+33x-243=0 | | 7-20=6x-5-5x | | [m+4]+4=14 | | 12=3x-16 | | y^2-12y+36=100 | | 8+10x+2x=3+12x | | [m+4]+6=24 | | 5t+11=7t-15 | | 4x+8=2(x+6) | | 9y-3=6y+6 | | 147-6x=30x+19 | | 42-4t=12+6t |

Equations solver categories